Understanding reading and learning from multi-representational texts in a second language - Binti Mohd Jaafar, Nurjanah (2020)
This thesis explores how learners read and learn from text and pictures in a second language. Although research into multi-representational materials has developed substantially in recent years, there is a tendency to focus mainly on first language (L1) learners. Less is known about how the growing population of second language (L2) learners engage and learn from these materials. To address this, an investigation into the reading behaviour of English as a second language speakers (or L2 readers) as well as its outcomes was conducted.